Livelihood strategies and the determinants of subjective wellbeing; A case study of subsistence farmers in the Northern region of Ghana - Yakubu, Abukari (2015)
A thesis submitted to the Department of Agricultural Economics, Agribusiness and Extension, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the degree of Master of Philosophy in Agricultural Economics.